PENGARUH BAURAN PEMASARAN JASA TERHADAP PEMBELIAN KARTU PERDANA DI KOTA LUBUKLINGGAU - Effendy, Muhammad (Universitas muhammadiyah palembang, 2012)
Formulation of the problem in this research is there are any influence of product, price, promotion and process to purchase SIM Card mobile operator company in Lubuklinggau Town. The purpose of this research is to know the influence of product, price, promotion and process to purchase SIM Card mobile opeartor company in Lubuklinggau Town. Type of this research is assosiation research that have relation of two variables which is independent variables and dependent variables. Independent variables used product, price, promotion and process whether have impact of independent variable which is purchasing decisions. Those variables developing become fifteen indicator. The data required are primer data which is the answer of respondent that obtained from the questionnaire. Whereas analysis technic used multiple linier regression. The result of this research conclude that there are influence of product, price, promotion and process which is significant of purchasing decisions to purcahes SIM card mobile operator company in Lubuklinggau.